2009
DOI: 10.1057/pm.2009.14
|View full text |Cite
|
Sign up to set email alerts
|

Managing money and retirement planning: Academics’ perspectives

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Overall, findings from this study showed that those who had a savings program for retirement were more confidents about their retirement. Lai, Lai and Lau (2009) conclude that those aged above 50 years are relatively more concerned about living expenses after retirement than those aged less than 30 years. Besides, there is significant difference between teaching position, education and age across the annual income levels from academicians' perspective.…”
Section: Literature Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…Overall, findings from this study showed that those who had a savings program for retirement were more confidents about their retirement. Lai, Lai and Lau (2009) conclude that those aged above 50 years are relatively more concerned about living expenses after retirement than those aged less than 30 years. Besides, there is significant difference between teaching position, education and age across the annual income levels from academicians' perspective.…”
Section: Literature Reviewmentioning
confidence: 85%
“…The similar study to this, VanDerHei & Olsen (2000); Joo & Pauwels (2002) found that males had higher confidence than female in planning for their retirement. In contrast, Tuan-Hock, et al (2011) andLai, Lai &Lau (2009) found that females tend to allocate more contributions for retirement saving.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 93%
“…Retirement planning is an individual's financial and non-financial preparation for their retirement life (Hanisch, 1995). Lai et al (2009) found that that lack of preparation for retirement will generally cause some form of disappointment during retirement. Although planning for retirement can be a challenging task, people are advised to do so as earlier as possible to guarantee a higher living standard in their golden years (Ng et al, 2011).…”
Section: Retirement Planning and Buying Intentionmentioning
confidence: 99%
“…The availability of income sources and potential resources after retirement are important considerations. Financial education and retirement planning provides an important basis for the development of new human resource policies in higher education and the importance of proper retirement planning, prior to retirement (Lai et al, 2009). These issues and challenges will be the key input to the sound retirement planning.…”
Section: Suggestion For Improvementmentioning
confidence: 99%